A tartaric acid pellet and a method for preparing the same
Patent Information
- Application Number
- CN202610884521.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-10-17
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]为了解决现有方法制得的酒石酸微丸圆整度和粒径均一性不佳的技术问题,本发明提供了一种酒石酸微丸的制备方法
(1)本发明通过选用低取代羟丙甲纤维素(L-HPMC)作为辅料,并配合特定的加水时机(在进行离心制粒前先将酒石酸与L-HPMC混合,水在离心制粒的过程中喷入),能够改善物料过快团聚的问题,从而提高酒石酸微丸的圆整度和粒径均一性,并确保其抗脆碎性。
Smart Images

Figure CN122954736A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of pharmaceuticals, and more particularly to a tartrate microsphere and its preparation method. Background Technology
[0002] Tartaric acid microspheres can be used as key and functional excipients in the pharmaceutical industry, serving as drug carriers to ensure dosage uniformity and increasing the bioavailability of weakly basic drugs. However, the preparation of tartaric acid microspheres using centrifugal granulation faces the following challenges: tartaric acid crystals have insufficient cohesion but readily self-adhede upon contact with water, leading to extreme situations during microsphere preparation where "low moisture content results in no granulation, while high moisture content leads to direct clumping," making it difficult to obtain microspheres with uniform particle size. Furthermore, tartaric acid powder exhibits a strong instantaneous water absorption effect upon contact with water, causing some binders to penetrate into the powder along with the water, while other binders rapidly concentrate and precipitate on the powder surface in localized areas. This results in excessively strong or insufficient adhesion in some areas of the tartaric acid powder surface, limiting the improvement of the sphericity of the tartaric acid microspheres.
[0003] Patent CN118178346A discloses a dabigatran mesylate capsule formulation and its preparation method. The capsule formulation comprises, from the inside out, a tartaric acid core, an isolation coating layer, a drug-loaded coating layer, and a capsule shell. The tartaric acid core is composed of tartaric acid and a binder in a weight ratio of 93-97:3-7. The binder is one or more of low-substituted hydroxypropyl cellulose, hydroxypropyl methylcellulose, sucrose, or pregelatinized starch in any proportion. This patent uses a method of mixing tartaric acid, binder, and water followed by centrifugal granulation to prepare the tartaric acid core. In this method, the tartaric acid powder readily agglomerates upon contact with water, resulting in poor sphericity and a wide particle size distribution of the prepared microspheres. Furthermore, in the adhesives used in this patent, low-substituted hydroxypropyl cellulose and ordinary hydroxypropyl cellulose readily swell rapidly in water to form a high-viscosity gel under the action of hydroxypropoxy groups; ordinary hydroxypropyl methylcellulose has an excessively high content of substituents and also easily forms a high-viscosity colloid when exposed to water; sucrose dissolves rapidly in water to form a highly concentrated sugar solution, and its viscosity increases rapidly; pregelatinized starch gelatinizes rapidly in water and becomes thicker, and its gel viscosity takes effect quickly—the rapid high viscosity characteristics of these adhesives, combined with the strong self-adhesiveness of tartaric acid powder, easily cause powder agglomeration and uneven local adhesion, which will further affect the sphericity and particle size uniformity of tartaric acid microspheres. Summary of the Invention
[0004] To address the technical problem of poor sphericity and particle size uniformity in tartrate microspheres prepared by existing methods, this invention provides a method for preparing tartrate microspheres. Using the method of this invention, the prepared tartrate microspheres can achieve more uniform particle size and higher sphericity.
[0005] The specific technical solution of this invention is as follows: In a first aspect, the present invention provides a method for preparing tartrate microspheres, comprising the following steps: S1: Tartaric acid and low-substituted hydroxypropyl methylcellulose are mixed to obtain a mixed powder; the mass percentage of tartaric acid in the mixed powder is not less than 90%; S2: The mixed powder is centrifuged and granulated, with water sprayed in during the process, to prepare micro-pellets.
[0006] In this invention, low-substituted hydroxypropyl methylcellulose (L-HPMC) is selected as an excipient (binder), and with specific timing of water addition (tartaric acid is mixed with L-HPMC before centrifugation granulation, and water is sprayed in during the centrifugation process), the problem of rapid material agglomeration can be improved, thereby enhancing the sphericity and particle size uniformity of tartaric acid microspheres. The specific mechanism is as follows: Hydroxypropyl cellulose (HPC) contains only hydroxypropoxy groups, which cause it to swell rapidly upon contact with water, forming a high-viscosity gel. This, combined with the strong self-adhesive properties of tartaric acid powder, leads to uncontrolled agglomeration of the material, affecting the sphericity and particle size uniformity of tartaric acid pellets. In contrast, the methoxy groups in hydroxypropyl methylcellulose (HPMC) act as hydration retarders, slowing down its swelling rate upon contact with water and moderately reducing its viscosity. Furthermore, the relatively low substituent content in L-HPMC also helps prevent it from forming a high-viscosity colloid too quickly upon contact with water. Based on this, the present invention pre-mixes tartaric acid with L-HPMC without adding water before centrifugal granulation, and then sprays water during centrifugal granulation. This utilizes the physical barrier effect of L-HPMC powder to inhibit the self-adhesion of tartaric acid upon contact with water to a certain extent. At the same time, L-HPMC can provide appropriate interparticle bonding force after contact with water during centrifugal granulation, which is suitable for the continuous process of powder deposition of "wetting, deposition and forming at the same time". This can improve the sphericity and particle size uniformity of tartaric acid microspheres and ensure their resistance to brittleness.
[0007] As an optional implementation, the preparation method specifically includes the following steps: S1: Take tartaric acid, low-substituted hydroxypropyl methylcellulose and purified water. Grind the tartaric acid and sieve it. Mix the tartaric acid and low-substituted hydroxypropyl methylcellulose using an equal-incremental mixing method to obtain a mixed powder. The mass percentage of tartaric acid in the mixed powder shall not be less than 90%. S2: Place the mixed powder in a centrifugal granulation device, spray in purified water, and prepare micro-pellets; S3: Dry the micro-pellets and sieve them.
[0008] As an optional implementation, in step S1, the low-substituted hydroxypropyl methylcellulose contains 7.0-9.9% hydroxypropoxyl and 8.0-16.0% methoxyl.
[0009] The content of each substituent in L-HPMC mentioned in this invention refers to the mass fraction of that substituent in L-HPMC.
[0010] The content of hydroxypropoxy and methoxy groups in L-HPMC comprehensively affects its hydration behavior, swelling behavior, and adhesive properties, thus influencing the final performance of the tartrate microspheres. The influencing factors are complex and multifaceted, for example: (1) By replacing some of the hydroxyl groups in cellulose with hydroxypropoxy and methoxy, the hydrogen bonds between cellulose molecules can be reduced, thereby improving its hydration and swelling properties and increasing the interfacial adhesion sites. However, when the content of hydroxypropoxy and methoxy in L-HPMC is too high (too many hydroxyl groups in cellulose are replaced), the cold water solubility of L-HPMC will be enhanced, and it will easily form a high-viscosity colloid, causing tartaric acid powder to agglomerate and stick to the wall, resulting in poor sphericity and poor particle size uniformity of microspheres.
[0011] (2) When the proportion of hydroxypropoxy and methoxy is too large, L-HPMC will easily swell and become sticky, causing tartaric acid powder to agglomerate and stick to the wall, resulting in poor sphericity and uneven particle size of microspheres. When the proportion of methoxy is too large, L-HPMC will have insufficient hydration capacity, and water will be quickly taken away by tartaric acid, leading to local supersaturation and recrystallization of tartaric acid. In addition, water will penetrate into the interior of tartaric acid powder too quickly, which will also make it difficult to form a uniform bond between the surface of the tartaric acid powder to be laminated and the microsphere growth interface. The above factors will result in excessively brittle microspheres and poor particle size uniformity.
[0012] This invention controls the hydroxypropoxy and methoxy content in L-HPMC to 7.0~9.9% and 8.0~16.0%, respectively, which can control the hydration behavior, swelling behavior and adhesion properties of L-HPMC at appropriate levels, improve the uniformity and stability of interfacial adhesion of tartaric acid powder during centrifugal lamination, and make the resulting pellet cores have higher roundness, brittleness resistance and particle size uniformity.
[0013] As an optional implementation, in step S1, the mixed powder includes mixed powder I and mixed powder II, wherein the hydroxypropoxy content of the low-substituted hydroxypropyl methylcellulose used is 7.0~8.0% and 8.5~9.9%, respectively; the specific process of step S2 includes: S2.1: Place the mixed powder I in a centrifugal granulation device, start spraying water to perform centrifugal granulation, until the mixed powder I is fully wetted; S2.2: Continue centrifugal granulation, continuously adding mixed powder I and water during the process to obtain masterbatch; S2.3: Continue centrifugation and granulation, continuously adding mixed powder II and water during the process.
[0014] In the masterbatch preparation process (steps S2.1 and S2.2), L-HPMC with a relatively low hydroxypropoxy content (7.0~8.0%) is used. It is less prone to excessive swelling and stickiness when exposed to water, which helps to inhibit material agglomeration, wall adhesion, and disc adhesion during masterbatch preparation, ensuring that the masterbatch core is round and uniform, thus providing a foundation for the final formation of microspheres with high roundness and high particle size uniformity. In the masterbatch scale-up process (step S2.3), L-HPMC with a relatively high hydroxypropoxy content (8.5~9.9%) is used. It can provide stronger binding force, which is conducive to the formation of a continuous and dense binding layer during powder lamination, improving the strength of tartaric acid microspheres and giving them higher resistance to brittleness (i.e., lower brittleness).
[0015] As an optional implementation, in steps S2.1 and S2.2, the conditions for centrifugal granulation are: air volume of 10-30%, main unit speed of 100-200 rpm, peristaltic pump delivering purified water at a speed of 2-8 rpm, and atomization pressure of 0.05-0.3 MPa.
[0016] As an optional implementation, in step S2.3, the conditions for centrifugal granulation are: the main unit speed is 100~200 rpm, and the peristaltic pump delivers purified water at a speed of 8~15 rpm.
[0017] As an optional implementation, the mass ratio of the mixed powder I in step S2.1, the mixed powder I in step S2.2, and the mixed powder II in step S2.3 is 1:0.5~2:0.5~5.
[0018] As an optional implementation, in step S2, the mass ratio of the mixed powder to water is 100:2~8.
[0019] As an optional implementation, in step S1, the specific process of mixing tartaric acid and low-substituted hydroxypropyl methylcellulose using an equal-incremental method includes: S1.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them evenly to obtain mixed powder A; S1.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them evenly to obtain mixed powder B; S1.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them evenly to obtain mixed powder C; S1.4: Take mixed powder C and mix it evenly with the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder.
[0020] As an optional implementation, in step S1, the sieving is done through an 80-mesh sieve; in step S3, the drying conditions are: air inlet temperature of 100~120℃ and drying time of 45~60min.
[0021] Secondly, the present invention provides tartrate microspheres, which are prepared by the aforementioned preparation method.
[0022] Compared with the prior art, the present invention has the following advantages: (1) By using low-substituted hydroxypropyl methylcellulose (L-HPMC) as an excipient and coordinating with a specific timing of water addition (mixing tartaric acid with L-HPMC before centrifugation and spraying water in during centrifugation), the present invention can improve the problem of rapid agglomeration of materials, thereby improving the roundness and particle size uniformity of tartaric acid microspheres and ensuring their resistance to brittleness.
[0023] (2) By controlling the content of hydroxypropoxy and methoxy in L-HPMC to 7.0~9.9% and 8.0~16.0% respectively, the present invention can improve the sphericity, brittleness and particle size uniformity of tartrate microspheres by controlling the hydration behavior, swelling behavior and adhesion properties of L-HPMC to a suitable level.
[0024] (3) By using L-HPMC with a relatively low hydroxypropoxy content (7.0~8.0%) during the masterbatch production period and L-HPMC with a relatively high hydroxypropoxy content (8.5~9.9%) during the masterbatch scale-up period, the present invention can better balance the roundness, brittleness and particle size uniformity of tartrate pellets. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of a pellet core that passed the roundness test.
[0026] Figure 2 This is a schematic diagram of a pellet core that failed the roundness test. Detailed Implementation
[0027] The present invention will now be described through specific embodiments and comparative examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0028] Example 1
[0029] This embodiment prepares tartrate microcapsules according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose (7.0% hydroxypropoxy content and 15.8% methoxy content), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0030] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose in a mass ratio of 95:5).
[0031] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0032] S4: Drying The microspheres to be dried were placed in a boiling drying oven, the air inlet temperature was set to 115°C, and dried for 60 minutes to obtain the tartaric acid microspheres of this embodiment.
[0033] Example 2
[0034] The only difference between this embodiment and Example 1 is that the substituent content in the low-substituted hydroxypropyl methylcellulose is changed in this embodiment. Specifically, tartaric acid microspheres are prepared according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose (hydroxypropoxy content of 8.5% and methoxy content of 15.9%), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0035] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose in a mass ratio of 95:5).
[0036] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0037] S4: Drying The microspheres to be dried were placed in a boiling drying oven, the air inlet temperature was set to 115°C, and dried for 60 minutes to obtain the tartaric acid microspheres of this embodiment.
[0038] Example 3
[0039] The only difference between this embodiment and Embodiments 1 and 2 is that this embodiment uses the low-substituted hydroxypropyl methylcellulose from Embodiment 1 in the masterbatch preparation process (i.e., steps S3.1~S3.2 of Embodiments 1 and 2), and uses the low-substituted hydroxypropyl methylcellulose from Embodiment 2 in the masterbatch scale-up process (i.e., step S3.3 of Embodiments 1 and 2). Specifically, this embodiment prepares tartrate microspheres according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose, and purified water were prepared in a mass ratio of 95:5:8. The low-substituted hydroxypropyl methylcellulose consisted of two types: Low-substituted hydroxypropyl methylcellulose I (7.0% hydroxypropoxy group and 15.8% methoxy group) and Low-substituted hydroxypropyl methylcellulose II (8.5% hydroxypropoxy group and 15.9% methoxy group). The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0040] S2: Preparation of mixed powder using the equal incremental mixing method I S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose I in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. I ; S2.2: Take mixed powder A at a mass ratio of 1:1 I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. I ; S2.3: Take mixed powder B at a 1:1 mass ratio I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C. I ; S2.4: Take mixed powder C I Mix the remaining low-substituted hydroxypropyl methylcellulose I and tartaric acid powder in a mass ratio of 8:31:1 for 5 minutes at a speed of 30 Hz to obtain mixed powder I (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose I in a mass ratio of 95:5).
[0041] S3: Preparation of Mixed Powder Using the Equal Incremental Mixing Method (II) S3.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose II in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. II ; S3.2: Take mixed powder A at a mass ratio of 1:1 II Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. II ; S3.3: Take mixed powder B at a 1:1 mass ratio II Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C. II ; S3.4: Take mixed powder C II Mix the remaining low-substituted hydroxypropyl methylcellulose II and tartaric acid powder at a mass ratio of 8:31:1 for 5 minutes in a mixer at a speed of 30 Hz to obtain mixed powder II (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose II at a mass ratio of 95:5).
[0042] S4: Centrifugal granulation S4.1: Place the first part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S4.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S4.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S4.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add mixed powder II (the mass ratio of mixed powder II to mixed powder I is 2:3). During this process, continuously spray purified water to make the masterbatch grow continuously, and obtain micro pellets to be dried.
[0043] Example 4
[0044] The only difference between this embodiment and Example 3 is that the substituent content in the two types of low-substituted hydroxypropyl methylcellulose was changed. Specifically, in this embodiment, tartrate microspheres were prepared according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose, and purified water were prepared in a mass ratio of 95:5:8. The low-substituted hydroxypropyl methylcellulose consisted of two types: Low-substituted hydroxypropyl methylcellulose I (7.9% hydroxypropoxy group and 8.0% methoxy group) and Low-substituted hydroxypropyl methylcellulose II (9.9% hydroxypropoxy group and 8.3% methoxy group). The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0045] S2: Preparation of mixed powder using the equal incremental mixing method I S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose I in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. I ; S2.2: Take mixed powder A at a mass ratio of 1:1 I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. I ; S2.3: Take mixed powder B at a 1:1 mass ratio I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C.I ; S2.4: Take mixed powder C I Mix the remaining low-substituted hydroxypropyl methylcellulose I and tartaric acid powder in a mass ratio of 8:31:1 for 5 minutes at a speed of 30 Hz to obtain mixed powder I (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose I in a mass ratio of 95:5).
[0046] S3: Preparation of Mixed Powder Using the Equal Incremental Mixing Method (II) S3.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose II in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. II ; S3.2: Take mixed powder A at a mass ratio of 1:1 II Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. II ; S3.3: Take mixed powder B at a 1:1 mass ratio II Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C. II ; S3.4: Take mixed powder C II Mix the remaining low-substituted hydroxypropyl methylcellulose II and tartaric acid powder at a mass ratio of 8:31:1 for 5 minutes in a mixer at a speed of 30 Hz to obtain mixed powder II (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose II at a mass ratio of 95:5).
[0047] S4: Centrifugal granulation S4.1: Place the first part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S4.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S4.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S4.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add mixed powder II (the mass ratio of mixed powder II to mixed powder I is 2:3). During this process, continuously spray purified water to make the masterbatch grow continuously, and obtain micro pellets to be dried.
[0048] Example 5
[0049] The only difference between this embodiment and Example 3 is that the low-substituted hydroxypropyl methylcellulose used in Example 3 for masterbatch preparation (i.e., steps S3.1~S3.2 in Examples 1 and 2) and masterbatch scale-up (i.e., step S3.3 in Examples 1 and 2) are interchanged. Specifically, tartaric acid microspheres are prepared according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose, and purified water were prepared in a mass ratio of 95:5:8. The low-substituted hydroxypropyl methylcellulose consisted of two types: Low-substituted hydroxypropyl methylcellulose I (hydroxypropoxy group content 8.5%, methoxy group content 15.9%) and Low-substituted hydroxypropyl methylcellulose II (hydroxypropoxy group content 7.0%, methoxy group content 15.8%). The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0050] S2: Preparation of mixed powder using the equal incremental mixing method I S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose I in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. I ; S2.2: Take mixed powder A at a mass ratio of 1:1 I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. I ; S2.3: Take mixed powder B at a 1:1 mass ratio I Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C. I ; S2.4: Take mixed powder C I Mix the remaining low-substituted hydroxypropyl methylcellulose I and tartaric acid powder in a mass ratio of 8:31:1 for 5 minutes at a speed of 30 Hz to obtain mixed powder I (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose I in a mass ratio of 95:5).
[0051] S3: Preparation of Mixed Powder Using the Equal Incremental Mixing Method (II) S3.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose II in a 1:1 mass ratio, mix them in a mixer for 2 minutes at 30 Hz to obtain mixed powder A. II ; S3.2: Take mixed powder A at a mass ratio of 1:1 II Mix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder B. II ; S3.3: Take mixed powder B at a 1:1 mass ratio IIMix with tartaric acid powder in a mixer for 3 minutes at 30 Hz to obtain mixed powder C. II ; S3.4: Take mixed powder C II Mix the remaining low-substituted hydroxypropyl methylcellulose II and tartaric acid powder at a mass ratio of 8:31:1 for 5 minutes in a mixer at a speed of 30 Hz to obtain mixed powder II (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose II at a mass ratio of 95:5).
[0052] S4: Centrifugal granulation S4.1: Place the first part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S4.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of mixed powder I (accounting for 30% of the mass of mixed powder I obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S4.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S4.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add mixed powder II (the mass ratio of mixed powder II to mixed powder I is 2:3). During this process, continuously spray purified water to make the masterbatch grow continuously, and obtain micro pellets to be dried.
[0053] Comparative Example 1 The only difference between this comparative example and Example 1 is that this comparative example uses the method described in patent CN118178346A, where tartaric acid, low-substituted hydroxypropyl methylcellulose, and purified water are mixed and then centrifuged to form granules. Specifically, this comparative example prepares tartaric acid microspheres according to the following steps: S1: Material preparation and mixing Tartaric acid, low-substituted hydroxypropyl methylcellulose (7.0% hydroxypropoxy group and 15.8% methoxy group), and purified water were mixed in a mass ratio of 95:5:45. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder. The low-substituted hydroxypropyl methylcellulose was evenly dispersed in purified water, and then tartaric acid was added and mixed evenly to obtain a mixture.
[0054] S2: Centrifugal granulation The mixture is placed in a centrifugal granulation and coating machine. The centrifugal granulation and coating machine is turned on for centrifugal granulation. The centrifugal granulation and coating machine is run for the same duration as steps S3.1 and S3.2 in Example 1 with the parameters set as 20% air volume and 150 rpm. Then, the main machine speed is gradually increased to 400 rpm and the machine is run for the same duration as step S3.3 in Example 1 to obtain micro-pellets to be dried.
[0055] S3: Drying The microcapsules to be dried were placed in a boiling drying oven, the inlet air temperature was set to 115℃, and dried for 60 minutes to obtain the tartaric acid microcapsules of this comparative example.
[0056] Comparative Example 2 The only difference between this comparative example and Example 1 is that the low-substituted hydroxypropyl methylcellulose is replaced with low-substituted hydroxypropyl cellulose. Specifically, tartaric acid microspheres were prepared in this comparative example according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl cellulose (hydroxypropoxy content of 7.0%), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0057] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and low-substituted hydroxypropyl cellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining low-substituted hydroxypropyl cellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and low-substituted hydroxypropyl cellulose in a mass ratio of 95:5).
[0058] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0059] S4: Drying The microcapsules to be dried were placed in a boiling drying oven, the inlet air temperature was set to 115℃, and dried for 60 minutes to obtain the tartaric acid microcapsules of this comparative example.
[0060] Comparative Example 3 The only difference between this comparative example and Example 1 is that the low-substituted hydroxypropyl methylcellulose is replaced with a high-substituted hydroxypropyl methylcellulose. Specifically, tartaric acid pellets were prepared in this comparative example according to the following steps: S1: Material preparation Tartaric acid, highly substituted hydroxypropyl methylcellulose (7.4% hydroxypropoxy content and 28.0% methoxy content), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0061] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and highly substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining highly substituted hydroxypropyl methylcellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and highly substituted hydroxypropyl methylcellulose in a mass ratio of 95:5).
[0062] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0063] S4: Drying The microcapsules to be dried were placed in a boiling drying oven, the inlet air temperature was set to 115℃, and dried for 60 minutes to obtain the tartaric acid microcapsules of this comparative example.
[0064] Comparative Example 4 The only difference between this comparative example and Example 1 is that the substituent content in the low-substituted hydroxypropyl methylcellulose was changed. Specifically, tartaric acid pellets were prepared in this comparative example according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose (hydroxypropoxy content of 6.6% and methoxy content of 5.6%), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0065] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose in a mass ratio of 95:5).
[0066] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0067] S4: Drying The microcapsules to be dried were placed in a boiling drying oven, the inlet air temperature was set to 115℃, and dried for 60 minutes to obtain the tartaric acid microcapsules of this comparative example.
[0068] Comparative Example 5 The only difference between this comparative example and Example 1 is that the substituent content in the low-substituted hydroxypropyl methylcellulose was changed. Specifically, tartaric acid pellets were prepared in this comparative example according to the following steps: S1: Material preparation Tartaric acid, low-substituted hydroxypropyl methylcellulose (hydroxypropoxy content of 10.7% and methoxy content of 19.2%), and purified water were mixed in a mass ratio of 95:5:8. The tartaric acid was pulverized and passed through an 80-mesh sieve to obtain tartaric acid powder.
[0069] S2: Equal-volume incremental mixing method S2.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them in a mixer for 2 minutes at a speed of 30 Hz to obtain mixed powder A; S2.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder B; S2.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them in a mixer for 3 minutes at a speed of 30 Hz to obtain mixed powder C; S2.4: Take mixed powder C and the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder in a mass ratio of 8:31:1, mix them in a mixer for 5 minutes at a speed of 30 Hz to obtain mixed powder (composed of tartaric acid and low-substituted hydroxypropyl methylcellulose in a mass ratio of 95:5).
[0070] S3: Centrifugal granulation S3.1: Place the first part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) into a centrifugal granulation and coating machine, turn on the centrifugal granulation and coating machine to perform centrifugal granulation, and continuously spray purified water during the process. The operating parameters of the centrifugal granulation and coating machine are as follows: air volume is 20%, main unit speed is 150 rpm, peristaltic pump delivers purified water at a slow speed of 5 rpm, and atomization pressure is 0.1 MPa. S3.2: After the mixed powder placed in the centrifugal granulator coating machine is fully moistened (it can be formed into a ball when squeezed and dispersed when lightly pressed), the second part of the mixed powder (accounting for 30% of the mass of the mixed powder obtained in step S2) is slowly added. During this period, purified water is continuously sprayed in. The operating parameters of the centrifugal granulator coating machine are the same as in step S3.1. The powder addition speed is controlled according to the principle of being formed into a ball when squeezed and dispersed when lightly pressed throughout the process, so that the powder accumulates and masterbatch is obtained. S3.3: Gradually increase the main unit speed to 400 rpm, while simultaneously increasing the peristaltic pump speed to 10 rpm, and slowly add the third part of the mixed powder (accounting for 40% of the mass of the mixed powder obtained in step S2). During this period, purified water is continuously sprayed in to make the masterbatch grow continuously, and micro-pellets to be dried are obtained.
[0071] S4: Drying The microcapsules to be dried were placed in a boiling drying oven, the inlet air temperature was set to 115℃, and dried for 60 minutes to obtain the tartaric acid microcapsules of this comparative example.
[0072] Test case The tartrate microspheres prepared in each example and comparative example were tested for their particle size distribution (Span value), friability, and sphericity. The testing methods are as follows: (1) Span value: The particle sizes D90, D50, and D10 of the tartrate microspheres were determined, and the Span value was calculated based on (D90-D10) / D50.
[0073] (2) Friability: After sieving the tartrate microspheres to be tested according to their particle size specifications, take the sample on the lower limit sieve as the test sample, weigh the test sample m1 (6.5g) accurately; weigh two parallel samples, and add the weighed samples to the friability tester (each drum contains 20 3mm stainless steel beads), start the friability tester and run it for 4 minutes and then stop, the speed is 25 rpm, after which take out the sample in the drum and place it on the lower limit sieve of the sample to be tested and sieve it, weigh the weight m2 of the sample on the sieve, and calculate the friability of the sample according to (m1-m2) / m1×100%.
[0074] (3) Roundness: Lay the pellet cores flat on a petri dish; visually observe them using a microscope (magnification 10×4, 10×5, or 10×10), selecting pellet cores with intact edges within the field of view for observation; observe at least 40 pellet cores by taking different fields of view, and count the total number of pellet cores that fail the appearance test (the appearance of a qualified pellet core under the microscope is as follows). Figure 1 As shown, the substandard pellet cores appear under a microscope as follows: Figure 2 (As shown); the roundness of the pellet core is calculated as follows: .
[0075] The test results are shown in Table 1.
[0076] Table 1 Performance test results of tartrate microcapsules
[0077] Based on the test results in Table 1, it can be seen that: (1) Compared with Comparative Example 1, the tartaric acid microspheres prepared in Example 1 have a smaller Span value and higher sphericity. The main reason is that Comparative Example 1 uses a method of mixing tartaric acid, binder and water and then centrifuging to granulate. Tartaric acid powder is very prone to self-adhesion and agglomeration when it comes into contact with water, resulting in poor sphericity and particle size uniformity of the microspheres. However, in Example 1, tartaric acid and L-HPMC are mixed in advance without adding water before centrifugation and water is sprayed in during centrifugation. The physical barrier effect of L-HPMC powder can be used to inhibit the self-adhesion of tartaric acid when it comes into contact with water to a certain extent.
[0078] (2) Compared with Comparative Example 2, the tartaric acid microspheres prepared in Example 1 have a smaller Span value and higher sphericity. The main reason is that the excipient used in Comparative Example 2 is low-substituted hydroxypropyl cellulose. Since the substituent is only hydroxypropoxy, it will quickly swell to form a high-viscosity gel after contact with water. This, combined with the strong self-adhesiveness of tartaric acid powder, will cause the material to easily agglomerate uncontrollably, affecting the sphericity and particle size uniformity of the tartaric acid microspheres. In contrast, L-HPMC was used in Example 1. The methoxy group in L-HPMC can play a hydration retardation role, slowing down its swelling rate when it comes into contact with water and moderately reducing its viscosity, thereby improving the problem of the material agglomerating too quickly.
[0079] (3) Compared with Comparative Example 3, the tartaric acid microspheres prepared in Example 1 have a smaller Span value and lower brittleness. The main reason is that the L-HPMC used in Comparative Example 3 has an excessively high methoxy content without changing the hydroxypropoxy content, which will cause insufficient hydration capacity of L-HPMC. The water is easily grabbed by tartaric acid, resulting in local supersaturation and recrystallization of tartaric acid. In addition, the water penetrates into the interior of the tartaric acid powder too quickly, which will also make it difficult to form a uniform bond between the surface of the tartaric acid powder to be laminated and the microsphere growth interface. The above factors will cause the obtained microspheres to be too brittle and have poor particle size uniformity.
[0080] (4) Compared with Comparative Example 4, the tartaric acid microspheres prepared in Example 1 have lower brittleness. The main reason is that the total content of substituents in the L-HPMC used in Comparative Example 4 is too low, which will form more intermolecular hydrogen bonds, resulting in poor hydration and swelling properties, which will cause fewer interfacial adhesion sites and affect the adhesion strength between tartaric acid powders.
[0081] (5) Compared with Comparative Example 5, the tartaric acid microspheres prepared in Example 1 have a smaller Span value and higher sphericity. The main reason is that the total content of substituents in the L-HPMC used in Comparative Example 5 is too high, which will increase the cold water solubility of L-HPMC, easily form a highly viscous colloid, cause tartaric acid powder to agglomerate and stick to the wall, and thus result in poor sphericity and poor particle size uniformity of the microspheres.
[0082] (6) Compared with Examples 1, 2 and 5, Examples 3 and 4 can better balance the uniformity of tartaric acid microspheres in terms of particle size, resistance to brittleness and roundness. The main reason is that: in the masterbatch process, L-HPMC with a relatively low hydroxypropoxy content is used, which is not prone to excessive swelling and sticking when exposed to water. This helps to inhibit material agglomeration, wall adhesion and disk adhesion during masterbatch process, ensuring the roundness and uniformity of the masterbatch core, and providing a foundation for the final formation of microspheres with high roundness and high particle size uniformity; in the masterbatch scale-up process, L-HPMC with a relatively high hydroxypropoxy content is used, which can provide stronger adhesion, which is conducive to the formation of a continuous and dense adhesive layer during powder lamination, improving the strength of tartaric acid microspheres and giving them higher resistance to brittleness.
Claims
1. A method for preparing tartrate microspheres, characterized in that, Includes the following steps: S1: Tartaric acid and low-substituted hydroxypropyl methylcellulose are mixed to obtain a mixed powder; the mass percentage of tartaric acid in the mixed powder is not less than 90%; S2: The mixed powder is centrifuged and granulated, with water sprayed in during the process, to prepare micro-pellets.
2. The preparation method according to claim 1, characterized in that, Specifically, the following steps are included: S1: Take tartaric acid, low-substituted hydroxypropyl methylcellulose and purified water. Grind the tartaric acid and sieve it. Mix the tartaric acid and low-substituted hydroxypropyl methylcellulose using an equal-incremental mixing method to obtain a mixed powder. The mass percentage of tartaric acid in the mixed powder shall not be less than 90%. S2: Place the mixed powder in a centrifugal granulation device, spray in purified water, and prepare micro-pellets; S3: Dry the microspheres and sieve them.
3. The preparation method according to claim 1 or 2, characterized in that, In step S1, the low-substituted hydroxypropyl methylcellulose contains 7.0-9.9% hydroxypropoxyl and 8.0-16.0% methoxyl.
4. The preparation method according to claim 3, characterized in that, In step S1, the mixed powder includes mixed powder I and mixed powder II, wherein the hydroxypropoxy content of the low-substituted hydroxypropyl methylcellulose used is 7.0~8.0% and 8.5~9.9%, respectively; the specific process of step S2 includes: S2.1: Place the mixed powder I in a centrifugal granulation device, start spraying water to perform centrifugal granulation, until the mixed powder I is fully wetted; S2.2: Continue centrifugal granulation, continuously adding mixed powder I and water during the process to obtain masterbatch; S2.3: Continue centrifugation and granulation, continuously adding mixed powder II and water during the process.
5. The preparation method according to claim 4, characterized in that: In steps S2.1 and S2.2, the conditions for centrifugal granulation are: air volume of 10-30%, main unit speed of 100-200 rpm, peristaltic pump delivering purified water at a speed of 2-8 rpm, and atomization pressure of 0.05-0.3 MPa. In step S2.3, the conditions for centrifugal granulation are: the main unit speed is 100~200 rpm, and the peristaltic pump delivers purified water at a speed of 8~15 rpm.
6. The preparation method according to claim 4, characterized in that, The mass ratio of the mixed powder I in step S2.1, the mixed powder I in step S2.2, and the mixed powder II in step S2.3 is 1:0.5~2:0.5~5.
7. The preparation method according to claim 1 or 2, characterized in that, In step S2, the mass ratio of the mixed powder to water is 100:2~8.
8. The preparation method according to claim 2, characterized in that, In step S1, the specific process of mixing tartaric acid and low-substituted hydroxypropyl methylcellulose using the equal-increment method includes: S1.1: Take tartaric acid powder and low-substituted hydroxypropyl methylcellulose in a 1:1 mass ratio, mix them evenly to obtain mixed powder A; S1.2: Take mixed powder A and tartaric acid powder in a 1:1 mass ratio, mix them evenly to obtain mixed powder B; S1.3: Take mixed powder B and tartaric acid powder in a 1:1 mass ratio, mix them evenly to obtain mixed powder C; S1.4: Take mixed powder C and mix it evenly with the remaining low-substituted hydroxypropyl methylcellulose and tartaric acid powder.
9. The preparation method according to claim 2, characterized in that, In step S1, the sieving is done through an 80-mesh sieve; in step S3, the drying conditions are: air inlet temperature of 100~120℃ and drying time of 45~60min.
10. A tartrate microcapsule, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.